Family dysfunction and some associated factors among adolescent students of three municipalities of Antioquia - Colombia (2014)
ABSTRACT: Family dysfunction is a concern of the educational sector in Colombia, adolescents are affected by stressful situations into a family, this leads to having a poor school performance; this paper focuses to identify some mental health factors associated with family dysfunction in school teenagers in 2010. A cross-sectional association study was conducted with a random sample of 1411 high school students between 11 and 19 years old, were used as data collection instrumentsto measure risk suicide, psychoactive substance use, depression, vulnerability and family functioning. Using a logistic regression model, it was identified that the variables that best explain family dysfunction are: the presence of depression, risk in suicidal orientation,and vulnerability in family cohesion, family routines, adolescent's participation in problem solving, communication with mother and father, the feeling of happiness and support adolescents. The research shows that family adversities, the presence of risk of suicidal orientation and the presence of depression, affect the proper functioning of the family schooled teenager.